Physicochemical and Organoleptic Characteristics of Jelly Drink Produced from Lamtoro Gung (Leucaena leucocephala) Seed Juice, Pineapple Juice, and Kappa Carrageenan - Vania Tiara Salsabila; Ulya Sarofa; Riski Ayu Anggreini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
In this study, jelly drink was produced using lamtoro gung seed juice as a plant-based protein source, proportioned with pineapple juice to enhance aroma and flavor, and kappa carrageenan as a hydrocolloid to form the gel texture of the jelly drink. This study was an experimental research aimed at determining the effects of the proportions of lamtoro gung juice and pineapple juice, as well as the addition of kappa carrageenan, on the physicochemical and organoleptic characteristics of the jelly drink. The study employed a factorial Completely Randomized Design (CRD) with two factors and two replications. Factor I was the proportion of lamtoro gung juice to pineapple juice (60:40, 50:50, and 40:60), while Factor II was the concentration of kappa carrageenan (0.2%, 0.3%, and 0.4%). Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The best treatment was obtained from the proportion of lamtoro gung juice to pineapple juice of 40:60 with the addition of 0.4% carrageenan. This treatment exhibited favorable physicochemical and organoleptic characteristics, including moisture content (77.575%), total solids (22.675%), pH (4.69), total soluble solids (21 °Brix), protein content (0.935%), antioxidant activity (63.12%), vitamin C content (17.89%), syneresis (39.345%), viscosity (630), and hedonic scores for color 3.84 (neutral to slightly liked), aroma 3.36 (neutral to slightly liked), taste 3.84 (neutral to slightly liked), and texture 3.84 (neutral to slightly liked). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3 – Good Health and Well-BeingSDG 9 – Industry, Innovation, and InfrastructureSDG 12 – Responsible Consumption and Production